The life and crimes of Bernetta Wallflower : a novel - Graff, Lisa (Lisa Colleen), 1981- (Laura Geringer Books, 2008)
After her supposed best friend implicates her in a cheating and blackmail scam, twelve-year-old Bernie loses her private school scholarship but, with the help of a new friend, spends the summer using her knowledge of magic and sleight-of-hand both to earn the $9,000 in tuition money and to get revenge.